2014
DOI: 10.1016/j.annepidem.2014.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and risk of all-cause mortality among patients with tuberculosis in the state of Georgia, 2009–2012

Abstract: Purpose To estimate the association between diabetes mellitus (DM) and all-cause mortality during tuberculosis (TB) treatment. Methods From 2009 to 2012 a retrospective cohort study among reported TB cases in Georgia was conducted. Patients aged ≥16 years were classified by DM and HIV status at time of TB diagnosis and followed during TB treatment to assess mortality. Hazard ratios (HR) were used to estimate the association between DM and death. Results Among 1,325 patients with TB disease, 151 (11.4%) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
21
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
6
21
0
3
Order By: Relevance
“…Diabetes mellitus was a strong indicator for treatment failure and mortality in general pulmonary tuberculosis patients (34)(35)(36)(37). No studies in acute respiratory failure confirmed this finding.…”
Section: Discussionmentioning
confidence: 70%
“…Diabetes mellitus was a strong indicator for treatment failure and mortality in general pulmonary tuberculosis patients (34)(35)(36)(37). No studies in acute respiratory failure confirmed this finding.…”
Section: Discussionmentioning
confidence: 70%
“…1315 Other studies have not observed significant differences between these groups. 16, 17 An important limitation of most studies to date is the reliance on self-reported DM status. Further, few studies have investigated the prevalence of pre-DM among patients with TB.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that DM prevalence among TB cases is variable. It ranges from about 50% reported by some studies in India, about 30% in Mexico, less than 10% in the United States, to even lower values in certain African countries, Spain and China10111213141516. As reported levels of co-morbidity vary highly, National TB Control Programmes (NTPs) will need to decide whether such DM screening is needed.…”
mentioning
confidence: 99%